Ryzyko a wartość budżetów projektów badawczo-rozwojowych - Rokita, Sabina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The main aim of his article is to present problem with the R&D projects' risk management, particularly with including risk in budgets. There are described main areas of R&D projects' uncertainty, ways of assessing them, reacting to them and methods of including risk in budgets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 376-382